AGE AND WORK EXPERIENCES TO FATIQUE FEELINGS AND WORK PRODUCTIVITY RELATIONSHIP OF PALM OIL FRUIT BUNCH HARVEST WORKERS - Humaira' Kanajmi; Meizul Zuki; Damres Uker (Jurnal Agroindustri, 2017)
Purpose of this research was to analyze the correlation between the factor of age with fatigue of worker, the factor of working experience with fatigue of worker, the factor of age and working experience with fatigue of worker, and fatigue of workers with work productivity in palm oil harvesting. Data were collectedby using quisionere. The analytical method used in this research is the analysis of correlation and linear regression.From the results of this study concluded that there was a significant, quite strong (r = 0.469) and in the same direction (positive) correlation between the age worker factor with fatigue of palm oil harvester by linear regression equation ????1 = 2,571 + 0,077 X1, there was a significant, but low (r = -0.344) and not in the same direction (negative) correlation between the factor of working experience with fatigue of palm oil harvester by  linear  regression equation ????1 =  6,303 -  0,067  X2, there  was  a significant  and  very  strong correlation (R = 0.922) between factors of age and working experience with fatigue of  palm oil harvester  by  linear regression  equation ????1 =  0,742  +  0,178  X1   -  0,195  X2,  and  there  was  a significant, but low (r = -0.271) and not in the same direction (negative) correlation between the fatigue of workers with productivity of palm oil harvesting by linear regression equation ????2 = 258,45- 6,979 X. Labor of palm oil harvesting should be managed by factor age of workers and work experience in order to minimize fatigue of workers so that can improve productivity.